Joko Widodo’s English Pronunciation: Phonological Review - Suhardianto; Mardiana, Diand; Oktafiani, Susi (JOLADU: Journal of Language Education, 2023)
ABSTRACT Verbal communication can not be separated from the sound (pronunciation) process of the language. This research aims to find the problem of vowel and consonant sounds pronounced by Mr. Joko Widodo in his speech. This research is a qualitative descriptive study. In collection of data, the researchers use observation method or refer to the technique of simak bebas libat cakap where the process of collecting data is done by listening to the pronunciation of the words and researchers are not involved directly. In analyzing data, the researchers used the method of identity with articulation phonetic techniques. The process of presenting the research results used formal and informal methods by words (descriptively) and tables. From the process of analyzing data results, can be found 1. Mr Jokowi difficulties in pronouncing diphthong /eɪ/, /aʊ/ and /əʊ/ 2. Mr Jokowi difficulties in saying consonant /θ/, /ð/, /v/, /z/, /ʃ/ 3. Mr Jokowi can not say some consonant in the end of the word 4. Mr. Jokowi changes the consonant -y sound at the end of the word become /e/ 5. Mr Jokowi changes vowel /ə/ becomes /o/.